Comparison of Visual Outcome and Morphologic Change between Different Surgical Techniques in Idiopathic Epiretinal Membrane Surgery - Yo-Chen Chang; Chia-Ling Lee; Kuo-Jen Chen; Li-Yi Chiu; Tzu-En Kao; Pei-Kang Liu; Kwou-Yeung Wu; Wen-Chuan Wu (Journal of Ophthalmology)
Purpose. To investigate the morphological and functional outcomes of idiopathic epiretinal membrane (ERM) surgery between three different surgical techniques: ERM peeling only, whole-piece ILM peeling, and maculorrhexis ILM peeling. Patients and Methods. This is a retrospective, consecutive, and comparative study enrolling 60 patients from Kaohsiung Medical University Hospital, Kaohsiung, Taiwan. Surgery performed between July 2011 and June 2012 was done with ERM peeling only (group I). ERM peeling and ILM peeling as a whole piece (group II) were performed between July 2012 and July 2013. Surgery performed between August 2013 and December 2014 was done with maculorrhexis ILM peeling (group III). Main outcome measures include visual acuity change (BCVA) and central foveal thickness (CFT). Results. At 12 months postoperation, the mean BCVA in group III was significantly better than in group I and group II. Comparison of CFT reduction between the three groups revealed significantly more reduction in group III than in group II at all postoperative follow-up periods. Eyes with restoration of foveal depression were observed in 52.6% in group I, 52.4% in group III, but only 20% of eyes in group II. None of the eyes in both ILM peeling groups encountered recurrence of macular pucker formation. Conclusion. All three techniques can achieve visual acuity improvement and macular thickness reduction. Maculorrhexis ILM peeling achieves more rapid improvement of visual function, better final visual outcome, and a higher rate of normal foveal contour than whole-piece ILM peeling.